Modeling Harmony: Music, Theology, and Peace-Building - Begbie, Jeremy (Interpretation, 2017)
This article explores the ways music might serve as both a vehicle and a model of God’s peacemaking, the peace God intends and has made possible between groups in conflict. Attention to various senses and types of musical harmony can do much to illuminate and clarify different conceptions of peace and peace-building already in use, as well as generate fresh and perhaps neglected ways of conceiving them and practicing peacemaking in the future.